Protective coloration in the coleoptera - Peairs, Leonard Marion (My University, 1905)
Introduction: One of the fundamental laws of nature is the arrangement by virtue of which every living thing has its natural enemies from which it must be protected or suffer the extinction of the species. These so called enemies are not, of course, enemies because of hatred or spite, as are enemies in the human family, but the enmity is rather the result if the natural instinct of some species to secure their food by preying upon other species. In the economy of nature we find that it is not only the large and powerful animals that prey upon the: small and weak, but that there is a kind of provision for keeping the balance which works like an endless chain. This may be illustrated by taking a common case from nature. The larger carnivorous animals prey upon smaller animals which may in turn feed upon insects These insects: or their near relatives may in turn, be found gaining their living by sucking the blood of the first large flesh eating animals or living as parasites in or upon them, or by eating their carcasses after death. There seems to be a tendency always working toward the extinction of the weaker species by the more powerful ones, or by those of their own kind which are better adapted to the conditions of life in which they are placed. To counterbalance this tendency many of these smaller species acquire, or are provided with, some special adaptation to protect them from their foes, or to help them in their search for food. These adaptations take various forms. They may enable their possessor to run more swiftly so as to escape pursuit, or on the other hand they may enable some other animal to run or fill more swiftly and so more easily capture its prey. Another way by which an advantage is gained is by special means of concealment, on the one hand from the pursuers, and on the other, from the pursued.
Citation: Peairs, Leonard Marion. Protective coloration in the coleoptera. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Cryptic Colors; Warning Colors; Mimicry; Theses